PROPOSTA DE FATORES CRÍTICOS DE SUCESSO PARA A IMPLANTAÇÃO DE UM MODELO DE GESTÃO DA TECNOLOGIA DA INFORMAÇÃO: UM ESTUDO DE CASO NUMA INSTITUIÇÃO DE ENSINO FEDERAL - Moreira, Allan Winckler (2013)
The Information Technology (IT) has been an effective way to increase the agility in the administratives process and essencials services of a public instituition. In this context, the IT management is fundamental to monitor this scenario that is much more dependent on IT and to achieve excellence in the service to the users. The highlighted scenario has an object of research, federal institute of education, and the approach research propose the criticals factors of success to the implementation of a IT management model. Making the research, adobted, how metodology, the case study with a qualitative priority. First it was conducted a literature search to identify critical success factors (CSF) that influence in the implementation of a management model. Therefore, a semi-structured questionnaire was used to investigate whether the institution has practiced the control of any of the FCS in the literature and find out which is the perception of the servers compared to FCS to implement an IT management model, based on the Information Technology Infrastructure Library framework (ITIL). The results showed that many FCS found in the literature review are not applicable in the context of institution. Implementing an IT management model is required, as proposed, adopt some FCS as: top management support, involvement of stakeholders, indicators for monitoring results, etc. Therefore, the first steps that the institution can draw on to achieve the benefits and advantages that the implementation of an IT management model can bring is in the control and monitoring of FCS revealed by the survey.